2011
DOI: 10.1016/j.jcorpfin.2011.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Us knows us in the UK: On director networks and CEO compensation

Abstract: We analyze the relation between CEO compensation and networks of executive and nonexecutive directors for all listed UK companies over the period 1996-2007. We examine whether networks are built for reasons of information gathering or for the accumulation of managerial influence. Both indirect networks (enabling directors to collect information) and direct networks (leading to more managerial influence) enable the CEO to obtain higher compensation. Direct networks can harm the efficiency of the remuneration co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
69
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(82 citation statements)
references
References 40 publications
7
69
0
1
Order By: Relevance
“…The multiple directorships appointment could be seen as a proxy for director's reputation. Director with multiple directorships can be seen to have certain advantages over other such as resource exchange, control and influence over company's management (Renneboog & Zhao, 2011). Therefore, companies tend to appoint directors who are well-connected to other boardrooms (Barnea & Guedj, 2007).…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…The multiple directorships appointment could be seen as a proxy for director's reputation. Director with multiple directorships can be seen to have certain advantages over other such as resource exchange, control and influence over company's management (Renneboog & Zhao, 2011). Therefore, companies tend to appoint directors who are well-connected to other boardrooms (Barnea & Guedj, 2007).…”
Section: Descriptive Statisticsmentioning
confidence: 99%
“…Accordingly, we use the log of total assets to control for firm size. Furthermore, we use the average number of corporate affiliations of board members (Director Affiliations) as a proxy for board networks (Fich and Shivdasani, 2006;Larcker, So and Wang, 2013;Renneboog and Zhao, 2011). Finally, we control for average portfolio turnover of the top-five institutional investors (Institutional Investor Ownership Turnover), weighted by their percentage ownership, as a proxy for investor heterogeneity and heterogeneous investment horizons (Gaspar, Massa and Matos 2005).…”
Section: Control (Independent) Variablesmentioning
confidence: 99%
“…Stock-based compensation (SBC) has become an increasingly significant component of executive reward for UK CEOs, while the level of detail and complexity in the design of the stock-based element of pay has increased considerably since the mid-1980s (e.g. Buck et al, 2003;Conyon and Schwalbach, 2000;Goergen and Renneboog, 2011;Main, Bruce and Buck, 1996;Ozkan, 2011;Renneboog and Zhao, 2011). Recent empirical research documents the widespread use of relative performance evaluation (RPE) in stock-based incentive contracts where CEOs and managers are evaluated on the basis of peer performance and, in particular, the use of performance peer groups in restricted share schemes, performance share plans or long-term incentive plans (LTIPs) (Carter, Ittner and Zechman, 2009;Gong, Li and Shin, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The conception of CEOs in the literature traditionally has been dominated by the importance of developing and sustaining networks for improving organizational effectiveness (Lakshman, 2007 ). For instance, CEO networks were explored to determine compensation arrangements (Brown, Gao, Lee, & Stathopolous, 2012 ;Horton, Millo, & Serafeim, 2012 ;Renneboog & Zhao, 2011 ) and the propensity for mergers and acquisitions (e.g., Chikh & Filbien, 2011 ). With respect to CEOs' external networks, studies have found that peer-to-peer networking within a similar industry increased the economic value of the organizations (Chen et al, 2009 ;McDonald & Westphal, 2003 ).…”
Section: Ceo Networkmentioning
confidence: 99%